Analysis of functional magnetic resonance time-series in randomized event-related experiments - Choo, Keng Wah. (2008)
Functional magnetic resonance imaging (fMRI) measures changes in blood oxygenation and blood volume that result from neuronal activity. Deoxygenated hemoglobin acts as an endogenous parametric agent such that a reduction in the concentration of deoxygenated hemoglobin increases the T2*-weighted magnetic resonance signal.